2019
DOI: 10.14203/beritabiologi.v18i3.3709
|View full text |Cite
|
Sign up to set email alerts
|

Keanekaragaman Dan Kelimpahan Anggrek Epifit Di Kaki Gunung Liangpran, Kalimantan Timur

Abstract: Liangpran Mountain is located within the Heart of Borneo (HoB) Conservation Area which has high biodiversity. The exploration of orchids has been carried out in several locations in the HoB region and recorded a high diversity of wild orchid. This research was conducted to explore and inventory the orchids from the foothill of Mount Liangpran, and record  the diversity and abundance of epiphytic orchids in the study sites. This research was carried out by making track of exploration along the Nuyung river estu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
1
0
4
Order By: Relevance
“…Whereas the primary forest is dominated by tall trees with large trunk diameters, few branches and far from the ground, making it difficult to observe. According to Febriandito and Lita (2019), epiphytic orchids are often found on fallen trees, and according to research by Effendi et al (2019), trees with a trunk diameter of less than one meter were found to have 1-3 species of orchids consisting of 1-45 individuals, while in trees with a diameter of more than one meter only one individual orchid was found. Orchids are found in many branches and are rarely found in the branch-free zone.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the primary forest is dominated by tall trees with large trunk diameters, few branches and far from the ground, making it difficult to observe. According to Febriandito and Lita (2019), epiphytic orchids are often found on fallen trees, and according to research by Effendi et al (2019), trees with a trunk diameter of less than one meter were found to have 1-3 species of orchids consisting of 1-45 individuals, while in trees with a diameter of more than one meter only one individual orchid was found. Orchids are found in many branches and are rarely found in the branch-free zone.…”
Section: Resultsmentioning
confidence: 99%
“…Pada zona IV ditemukan 20 jenis anggrek epifit. Habitat yang cocok untuk pertumbuhan anggrek epifit adalah zona III dan zona IV (Effendi et al, 2019). Zona II merupakan daerah batang utama hingga batas percabangan.…”
Section: Jenis Pohon Inang Anggrek Epifitunclassified
“…Anggrek tersebut merupakan anggrek yang tidak memiliki pseudubolb. Hal tersebut sesuai dengan penelitian Effendi et al, (2019) bahwa pada zona V hanya ditemukan jenis anggrek yang berukuran kecil dan memiliki pseudubolb kecil atau tidak memiliki pseudobulb sama sekali.…”
Section: Jenis Pohon Inang Anggrek Epifitunclassified
See 2 more Smart Citations